Military Intervention, Coalition Governments and Economic Growth: Evidence from Turkey - M. Veysel KAYA; Erkan DEMİRBAŞ (Eurasian Journal of Business and Economics, 2012)
The aim of this study is to analyze the relation between military interventions, coalitions and economic growth. In the study the relation between foreign direct investment, unemployment and growth also analyzed. For this purpose a semi-log model is constructed and Ordinary Least Squares (OLS) method used to test the linear relation between military interventions, coalitions, certificates given to foreign companies for investment, unemployment and GDP per capita. According to the results of analysis, presence of the co-integration is confirmed in the long-run between mentioned variables. And it is found out that there is a negative and significant relation between unemployment, number of certificates given to foreign companies for investment, coalition and economic growth. The relation between military intervention and growth is found insignificant and negative. The VECM model was used to test the causality shows that during the transition process from short-run to long-run, balance will be established. Deviation of GDP per capita in the short-run will gravitate towards balance in the long-run.